Anti-cyberbullying interventions at school: comparing the effectiveness of gratitude and psychoeducational programmes - Chamizo-Nieto, María Teresa; Wallace-Ruíz, Agustín; Rey-Peña, Lourdes (Taylor & Francis, 2024)
Previous studies evidence the benefits of gratitude and psychoeducation to diminish the performing of aggressive behaviours. The aim of this study was to assess the effectiveness of a brief gratitude programme and a brief psychoeducational programme to prevent cyberaggression in adolescents. A sample of 483 adolescents (11–17 years old) participated in the study, being assigned to one of the following three groups: gratitude programme, psychoeducational programme and the control. Both programmes comprised four one-hour sessions. All participants completed the cyberaggression subscale of the European Cyberbullying Intervention Project Questionnaire (ECIP-Q) at three time points: pre-test, post-test and three-month follow-up. Significant decreases in cyberaggression were found at post-test in the psychoeducational group and at the three-month follow-up in the gratitude group. These findings provide the first evidence of the benefits of gratitude training in adolescents to prevent cyberaggression over time.
https://openpolicyfinder.jisc.ac.uk/id/publication/16284
Keywords: Agresividad en adolescentes; Gratitud - Aspectos psicológicos; Ciberacoso - Prevención; Gratitude intervention; Psychoeducation; Cyberaggression; Prevention; Adolescents